Activity of a trinuclear platinum complex in human ovarian cancer cell lines sensitive and resistant to cisplatin: cytotoxicity and induction and gene-specific repair of DNA lesions - Colella, G (Nature Publishing Group, 2001)
A collateral sensitivity or a very modest cross-resistance to BBR 3464 was found in 2 ovarian cancer cell lines with experimentally induced resistance to cisplatin. Loss of mismatch repair proteins (hMLH1, hPMS2) or overexpression of nucleotide excision repair proteins (ERCC1) was not detrimental for the cellular sensitivity to BBR 3464. Moreover, interesting differences in the kinetics of formation and removal of DNA lesions at the single-gene (N- ras) level were observed between BBR 3464 and CDDP. © 2001 Cancer Research Campaign www.bjcancer.com